Sensorimotor faculties bias choice behavior - Kubanek, Jan; Snyder, Lawrence H.; Abrams, Richard A. (Frontiers in Psychology, 2025)
Decision-making is a deliberate process that seemingly evolves under our own volition. Yet, research on embodied cognition has demonstrated that higher-order cognitive processes may be influenced, in unexpected ways, by properties of motor and sensory systems. Here we tested whether and how decisions are influenced by handedness and by asymmetries in the auditory system. Right- and left- handed participants performed an auditory decision task. In the task, subjects decided whether they heard more click sounds in the right ear or in the left ear, and pressed a key with either their right or left index finger, according to an instructed stimulus-key assignment (congruent or reversed). On some trials, there was no stimulus and subjects could choose either of the responses freely. When subjects chose freely, their choices were substantially governed by their handedness: Left-handed subjects were significantly biased to make the leftward choice, whereas right-handed subjects showed a substantial rightward bias. When the choice was governed by the sensory stimulus, subjects showed a rightward choice bias under the congruent key assignment, but this effect reversed to a leftward choice bias under the reversed key assignment. This result indicates a bias toward deciding that there were more clicks presented to the right ear. Together, our findings demonstrate that human choices can be influenced by properties of motor and sensory systems.